SUBSTANTIATION OF EXPEDIENCY OF THE SPECIFIC PREVENTION OF INFECTIOUS BRONCHITIS OF HENS - Гавриленко, О. С. (Scientific Progress & Innovations, 2015)
In the publication we presented data on the specific prevention of infectious bronchitis of hens, that is based on the use of specific drugs (vaccines), as well as the fulfilling common sanitary and veterinary measures. It was determined the period of conservation transovarial antibodies in blood serum of chicks-broilers and the optimal time for chicks’ vaccination, as well as we compared the effectiveness of the vaccine, made from different strains of infectious bronchitis virus of chickens.